2005
DOI: 10.1002/macp.200500090
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Polyelectrolyte Gels with Embedded Voids

Abstract: Summary: “Swiss‐cheese” polyelectrolyte gels, i.e., gels containing isolated voids filled with water were synthesized and studied. The gels were obtained by three‐dimensional copolymerization of neutral and charged monomers in the presence of oil/water emulsion stabilized by ionic surfactant. After removal of the surfactant and droplets of oil from the gel, the latter contains voids surrounded with charged swollen polymer network. Experiments were performed with slightly cross‐linked gels of copolymers of sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Thus, the gel collapse was unable to induce squeezing out of lipophilic phase when the emulsion droplets were “isolated” from each other by the continuous phase of the hydrogels cross-linked network. Yet more evidence in favor of TD droplets being separated from each other in the course of three-dimensional polymerization performed in the presence of emulsion has also been obtained earlier . For cryogel 3 and composite cryogel 4 the extent of the collapse was the same as for the control gel 1.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Thus, the gel collapse was unable to induce squeezing out of lipophilic phase when the emulsion droplets were “isolated” from each other by the continuous phase of the hydrogels cross-linked network. Yet more evidence in favor of TD droplets being separated from each other in the course of three-dimensional polymerization performed in the presence of emulsion has also been obtained earlier . For cryogel 3 and composite cryogel 4 the extent of the collapse was the same as for the control gel 1.…”
Section: Resultssupporting
confidence: 59%
“…The incorporation of diverse particles in the gels often imparts them new properties. Gels with entrapped magnetic particles are responsive to magnetic field, and gels containing clays have improved mechanical and adsorption properties. , Gels having isolated pores filled with water effectively trap linear macromolecules and low-molecular-weight multicharged ions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gels with entrapped magnetic particles are responsive to magnetic fields [6], gels containing clays have improved mechanical and adsorption properties [7]. Gels having isolated pores filled with water effectively trap linear macromolecules [8] and low-molecular-weight multi-charged ions [9][10]. Nevertheless, together with these advantages, the extensive study of smart gels demonstrated principal imperfections hampering their applications.…”
Section: Introductionmentioning
confidence: 99%
“…These systems are expected to be of significant practical interest as effective drug delivery systems 11. Besides, these composites were used for the preparation of polyelectrolyte networks containing voids or channels, so called “swiss‐cheese” gels 12–14. As it was showed, polymer matrix of composite gels can be formed either by the network of cross‐linked synthetic polymers, for instance, poly(acrylamide),12,13 or by physical gels, for instance, agarose‐based 15.…”
Section: Introductionmentioning
confidence: 99%